Equiangular line systems and switching classes containing regular graphs - Greaves, Gary Royden Watson (2019)
We develop the theory of equiangular lines in Euclidean spaces. Our focus is on the question of when a Seidel matrix having precisely three distinct eigenvalues has a regular graph in its switching class. We make some progress towards an answer to this question by finding some necessary conditions and some sufficient conditions. Furthermore we show that the cardinality of an equiangular line system in 18 dimensional Euclidean space is at most 60.